Reliability and availability study on substation automation system based on IEC 61850 - Yunus B.; Musa A.; Ong H.S.; Khalid A.R.; Hashim H. (2023)
The introduction of IEC61850 standards for substation automation requires the specification of the reliability and availability performance parameter. Presently, the methodology to calculate and verify the parameters is not readily available. This paper proposed a methodology to calculate the parameters at device level, bay level and substation level. The paper will propose suitable monitoring and evaluation of those parameters for future improvement. 2008 IEEE.